Pensar y sentir, dos modos no antagónicos de la razón en Descartes - Rocha, Leticia (Revista de Filosofía, 2008)
The concept of reason that Descartes offers is not restricted alone to the intuition and deduction of clear, evident contents, which form understanding. Reason, in addition to providing intelligence, also integrates the confusing elements of the soul-body composition: the internal and external sensations of the subject as his passions. Descartes contemplates these registers of human nature that enrich his theory of the mind and demystify its unilaterally rational character.